2021
DOI: 10.1007/s00477-021-02066-1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of normalized difference vegetation index (NDVI) to land surface temperature, soil moisture and precipitation over district Gautam Buddh Nagar, UP, India

Abstract: This study examines the trends in MODIS/TERRA derived Normalized Difference Vegetation Index (NDVI) and its correlation with Land Surface Temperature (LST), Soil Moisture (SM), and precipitation over Gautam Buddh Nagar (India), during the period 2005-2018. The region have a sub-humid and quite moderate climate, scattered into cultivable land, forest and fast growing urbanization zone, making it suitable for monitoring vegetation trends and its accompanying factors. The NDVI-derived vegetation growth patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…Flying platforms, including UAS and satellites, are widely used for measurements of the vegetation indices; particularly, satellites can be used for measuring the GPP and other parameters on an ecosystem and landscape scale. However, the efficiency of these indices, which can be quantitatively estimated on the basis of the coefficients of determination (for regressions connecting VIs and investigated parameters) and correlation can be varied from high to low values [111,112]. This variability in relations is caused by the influence of environmental conditions and geometry of measurements (some influencing factors are shown in Section 4).…”
Section: Reflectance Index Formula Referencesmentioning
confidence: 99%
“…Flying platforms, including UAS and satellites, are widely used for measurements of the vegetation indices; particularly, satellites can be used for measuring the GPP and other parameters on an ecosystem and landscape scale. However, the efficiency of these indices, which can be quantitatively estimated on the basis of the coefficients of determination (for regressions connecting VIs and investigated parameters) and correlation can be varied from high to low values [111,112]. This variability in relations is caused by the influence of environmental conditions and geometry of measurements (some influencing factors are shown in Section 4).…”
Section: Reflectance Index Formula Referencesmentioning
confidence: 99%
“…Normalized Difference Vegetation Index (NDVI) is used to find rainfall, LULCC, vegetation trend, surface air temperature, soil moisture etc [47]. Empirical study implies the highest percentage of vegetation of bare soil found to be 66% in 2010, water bodies & river found to be 6% in 2010, dense, healthy forest found to be 46% in year 2020 and shrub, and grassland area found to be 50% in year 1990.…”
Section: Normalized Difference Vegetation Index (Ndvi) Resultsmentioning
confidence: 99%
“…There is less study on the decadal change in the vegetation, Agriculture and land use pattern in the Nagavali basin, which has become pertinent as the manual assessment LULCC is time consuming, costly and the available ROR (Record of rights) are challenging. The use of satellite images and remote sensing tools have made the task easy, prompt and noncontroversial [38].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Global warming is the leading reason for climate change. Global temperature increases because of the rising of CO 2 concentration, water vapor, and other GHGs (Greenhouse gases) coming from fossil fuel burning and several anthropogenic activities (Sharma et al 2021 ; Ambade et al 2021 ; Gautam et al 2019a , b ). GHGs trap sunlight energy in the form of short waves and release it in a long wavelength.…”
Section: Effect Of Covid-19 On Human Healthmentioning
confidence: 99%